An Innovation of Islamic Religious Education in The Era of The Industrial Revolution 4.0 in Elementary School - Haidir Haidir; Muhammad Arizki; Miftah Fariz (Nazhruna: Jurnal Pendidikan Islam, 2021)
Learning Islamic religious education should not turn a blind eye to technological developments that are realized or not have a very large impact on life. Al-Ulum Private Elementary School Medan implements Islamic Religious Education learning innovations using and utilizing technological developments. For example, Teleconference, Google Classroom, Zoom Meeting by utilizing facilities such as e-mail (electronic mail), mobile phones, MP3 players, websites, blogging, search engines, and others. Learning models develop in the form of electronic learning (e-learning), electronic books (e-books), online classes, online discussions, computer-based learning. The use of whiteboards and markers, replaced with the use of Notebook media, LCD Projectors, and so on. Printed sourcebook materials, modules, and student worksheets are replaced with e-books, digital libraries, YouTube, and internet pages. This research is focused on qualitative research using descriptive method. This research intends to examine the natural role of Islamic Religious Education Learning Innovation in the Industrial Revolution Era 4.0 Studies at Al-Ulum Private Elementary School Medan. This research is suitable to use a qualitative research approach with a descriptive method, in revealing the facts as empirical truth in this research.